Rapport building: a pivotal art of academic discourse / Misyana Susanti Husin, Aini Andria Shirin Anuarudin and Lee Geok Imm - Husin, Misyana Susanti; Anuarudin, Aini Andria Shirin; Geok Imm, Lee (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Currently there is a surge of international students studying in Malaysian public universities who often face the challenges of adapting to social and cultural changes. The need for belongingness in class may be one of the anxiety-causing factors that might impede learning from taking place in the classroom especially for these foreign language (EFL) learners. Unfortunately, instructors seem to focus more on instructional strategies rather than establishing and maintaining rapport with their students. This study aims to investigate how rapport was constructed in EFL classrooms and the outcomes of the instructor-student rapport in class. The methods used consist of observations, audio recordings and semi-structured interviews with the instructors and students. Findings show that different strategies were used to establish rapport and there was a significant link between rapport and students’ learning behaviours and the enhancement of their receptivity to what was taught. Such impactful corollaries indeed warrant instructors ‘mastery of the art of establishing rapport with students. Other strategies for establishing instructor-student rapport are also discussed apart from the identified approaches